2017
DOI: 10.18632/oncotarget.17346
|View full text |Cite
|
Sign up to set email alerts
|

ING5 knockdown enhances migration and invasion of lung cancer cells by inducing EMT via EGFR/PI3K/Akt and IL-6/STAT3 signaling pathways

Abstract: ING5 belongs to the Inhibitor of Growth (ING) candidate tumor suppressor family, whose functions have been involved in the regulation of chromatin remodeling, cell cycle progression, proliferation and apoptosis. Our previous study has shown that ING5 overexpression inhibits lung cancer aggressiveness via suppressing epithelial to mesenchymal transition (EMT). However, the mechanisms remain largely unknown. In the current study, by Phospho-Kinase array and western blot, we have defined significantly upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…Many studies have reported on the niclosamide enhances cytotoxicity on various cancers, including oral cancer, lung cancer, colon, thyroid, cervix, ovarian, kidney, and prostate cancers, via STAT3, EGFR/PI3K/Akt, RANKL Wnt, mTOR, HIF‐1α/VEGF, Ras, c‐myc, and Notch signal pathways and mitochondria dysfunction 11, 12, 13, 14, 26, 27, 28, 29, 30, 31, 32, 33. Cancer cell upregulates other important downstream genes such as STAT3, which contributes to cell proliferation, cell survival, and angiogenesis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on the niclosamide enhances cytotoxicity on various cancers, including oral cancer, lung cancer, colon, thyroid, cervix, ovarian, kidney, and prostate cancers, via STAT3, EGFR/PI3K/Akt, RANKL Wnt, mTOR, HIF‐1α/VEGF, Ras, c‐myc, and Notch signal pathways and mitochondria dysfunction 11, 12, 13, 14, 26, 27, 28, 29, 30, 31, 32, 33. Cancer cell upregulates other important downstream genes such as STAT3, which contributes to cell proliferation, cell survival, and angiogenesis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Members of the ING family have been found to negatively regulate EGFR/PI3K/Akt signaling pathway, which is central to planaria neoblast re-population post IR [91,114]. Thus, the increased amount of IR-induced DNA damage together with upregulation of ING expression may act together to eliminate neoblast and prevent residual cell proliferation post-IR.…”
Section: Evolutionarily Conserved Dna Damage Repair Mechanisms Exist mentioning
confidence: 99%
“…Recently, the results of our studies and those of others have revealed that ING5 inhibits tumor progression and metastasis in lung, gastric, and breast cancers by inhibiting EMT. Using protein array, we have screened and confirmed that activation of both IL‐6/STAT3 and EGFR/PI3K/Akt signaling pathways is involved in ING5 knockdown‐promoted lung cancer invasiveness and EMT …”
Section: Introductionmentioning
confidence: 97%
“…Using protein array, we have screened and confirmed that activation of both IL-6/STAT3 and EGFR/PI3K/Akt signaling pathways is involved in ING5 knockdown-promoted lung cancer invasiveness and EMT. 14 Apart from PI3K/Akt and STAT3 oncogenic signaling pathways, hyperactivation of Wnt/β-catenin signaling is widely implicated in many types of cancers. 15,16 Our previous protein array results showed an increased β-catenin level in ING5 knockdown A549 cells, 14 suggesting that ING5 may also affect the β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%